Предмет:
МатематикаАвтор:
анонимНайдем производную функции:
(y)\' = ((2x - 1) / (4x + 4))\' = (2x - 1)\' * (4x + 4) - (4x + 4)\' * (2x - 1) / (4x + 4)^2 = (2 * (4x + 4) - 4 * (2x - 1)) / (4x + 4)^2 = (8x + 8 - 4x + 4) / (4x + 4)^2 = (4x + 12) / (4x + 4)^2 = (x + 3) / 4 * (x + 1)^2.
Подставим x0 = -5.
(y(-5))\' = (-5 + 3) / 4 * ( -5 + 1)^2 = -2 / 4 * 4^2 = -1 / 32.
Автор:
basileo6ozgДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть